Advances in Processing Kinetics for All‐Inorganic Halide Perovskite: Towards Efficient and Thermodynamic Stable Solar Cells. Issue 30 (14th September 2022) - Singh, Anupriya; Satapathi, Soumitra
Abstract: The all‐inorganic CsPbX3 (X—Cl, Br, I) perovskite has the potential to solve the practical issues of environmental instability due to the presence of hygroscopic organic cations in the hybrid organic–inorganic perovskites. The promising CsPbX3 perovskite exists in different crystallographic phases depending upon the composition and processing conditions which potentially impact the film morphology, device efficiency, and stability. Stabilizing the black metastable phase at room temperature has substantially solved the problem of high crystallization temperature, which is the main roadblock in managing the control over morphology and also the choice of the underlying charge transporting layers. Despite this progress, most of the works have not mentioned all the signatures of the metastable lower temperature black phase. In this focused review, the difference between the processing conditions to achieve different phases of not only the CsPbI3 but also the other halogen counterparts is analyzed. Additionally, progress done for each combination of halides is presented and the best processing conditions for each combination of halides are summarized. Finally, their photophysical properties are analyzed and the current state of inorganic perovskites in solar cell applications is presented, and a roadmap is put forward for all inorganic CsPbX3 perovskite‐based commercial photovoltaics devices. Abstract : In this review, the difference between the processing conditions to achieve different phases of not only the CsPbI3 but also the other halogen counterparts (CsPbI2Br, CsPbIBr2, CsPbBr3) is analyzed. An insightful discussion about the effect of composition and processing conditions on the film morphology, device efficiency, and stability is presented with a future roadmap for all inorganic CsPbX3 perovskite‐based commercial photovoltaics devices.